2015
DOI: 10.1177/0394632015592160
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin protected against the TNF-α-induced inhibition of osteogenic differentiation of human adipose-derived mesenchymal stem cells

Abstract: Cordycepin, 3'-deoxyadenosine, is an effective component isolated from the rare Chinese caterpillar fungus Cordyceps militaris. It exerts potent anti-inflammatory actions in different cell and animal models. However, its action remains unclear on the TNF-α-induced inhibition of osteogenic differentiation of adipose-derived mesenchymal stem cells (ADMSCs). In the present study, we demonstrated that cordycepin induced cell death at 20 and 40 μg/mL. Interestingly, 10 μg/mL cordycepin abrogated the cell death indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Based on the characteristics of cordycepin, we hypothesized that cordycepin might also have effect on cartilage metabolism. A previous study has shown that cordycepin has protection against inflammatory cytokine inhibition of osteogenic differentiation of human adipose-derived mesenchymal stem cells (19). A recent study has also demonstrated that cordycepin could prevent oxidative stress-induced inhibition of osteogenesis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the characteristics of cordycepin, we hypothesized that cordycepin might also have effect on cartilage metabolism. A previous study has shown that cordycepin has protection against inflammatory cytokine inhibition of osteogenic differentiation of human adipose-derived mesenchymal stem cells (19). A recent study has also demonstrated that cordycepin could prevent oxidative stress-induced inhibition of osteogenesis (20).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The direct inhibitory effect of TNFα on osteogenic differentiation in vitro was first proposed by Canalis in 1987. 11 Further studies including our previous report have demonstrated that TNFα inhibits osteogenic differentiation of a variety of mesenchymal stem cells (MSCs), such as bone marrow-derived MSCs, [12][13][14] human dental pulp stem cells, 15,16 human adipose-derived MSCs, 17 periodontal ligament stem cells [18][19][20] and C2C12 stem cells. 21 Moreover, an in vivo study showed that null for TNFα or its p55 receptor in mice significantly increased peak bone mass, resulting exclusively from elevated bone formation, indicating that TNFα potently suppressed bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Many signaling pathways, particularly nuclear factor kappaB (NF-κB) signaling, have been widely investigated in TNFα-induced osteogenesis inhibition. 13,14,17,23 Blockade of NF-κB signaling protects against TNFα-induced inhibition of osteogenic differentiation of cells, such as murine ST2 MSCs, human adipose-derived MSCs and C2C12 cells. 14,17,23 Therefore, the activation of NF-κB signaling plays a central role in TNFα-induced impairment of osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was also found to protect against cerebral ischemia injury 7 . A previous study indicated that cordycepin prevented the TNF-α-induced inhibition of osteogenic differentiation of human adipose-derived mesenchymal stem cells 8 . Nevertheless, the role of cordycepin on maintaining the pluripotency of ES and iPS cells was still unclear.…”
mentioning
confidence: 95%